PENGARUH PENYULUHAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN DAN SIKAP TENTANG PENYAKIT HIV/AIDS DI SMP BAZNAS PROVINSI SULAWESI SELATAN - Asfar, Akbar (Universitas Islam Negeri Alauddin Makassar, 2018)
HIV (Human Immunodeficiency Virus) is a virus that attacks the human immune system and then cause AIDS. While AIDS Acquired Immune Deficiency Syndrome may be defined as a collection of signs and symptoms of diseases caused by the loss or decrease of one's immune system. The purpose of this study was to determine the effect of health education on the level of knowledge and attitudes about HIV / AIDS in SMP BAZNAS Prov.Sul-Sel. The benefits of this research include the benefits of theoretical and practical benefits. This study is a pre-experimental design was a one-group pre-test - post-test. The population in this study as many as 72 people. Samples by using total sampling technique. Test the effect is done by using the Wilcoxon Signed Rank Test with significance level α <0.05. The results of this study indicate that there is the influence of health education on the level of knowledge about HIV / AIDS in SMP BAZNAS Prov.Sul-Sel (ρ = 0.000), and there is the influence of health education on attitudes about HIV / AIDS in SMP BAZNAS Prov.Sul-Sel ( ρ = 0.035). The conclusion of this study is the effect of health education on the level of knowledge and attitudes about HIV / AIDS in SMP BAZNAS Prov.Sul-Sel. The suggestions in this study is expected in the next researcher to replace or add other variables related to relationship health education about HIV / AIDS.